Diffusion of a Massive Quantum Particle Coupled to a Quasi-Free Thermal Medium - De Roeck, Wojciech; Fröhlich, Jürg (Communications in mathematical physics, 2011)
We consider a heavy quantum particle with an internal degree of freedom moving on the d-dimensional lattice $${{\mathbb Z}^d}$$(e.g., a heavy atom with finitely many internal states). The particle is coupled to a thermal medium (bath) consisting of free relativistic bosons (photons or Goldstone modes) through an interaction of strength λ linear in creation and annihilation operators. The mass of the quantum particle is assumed to be of order λ−2, and we assume that the internal degree of freedom is coupled “effectively” to the thermal medium. We prove that the motion of the quantum particle is diffusive in d ≥ 4 and for λ small enough.
Gesehen am 02.05.2022